Kemandirian Penyandang Disabilitas Netra melalui Program Kewirausahaan di Balai Rehabilitasi Sosial Penyandang Disabilitas Sensorik Netra Mahatmiya Bali - Muhaimin, Faris; Suwena, I Wayan; Aliffiati, . (Sunari Penjor : Journal of Anthropology; Vol 8 No 2 (2024): Volume 8. No. 2. September 2024, 2024)
Entrepreneurship training by the Social Rehabilitation Center for the Blind Sensory Disabled (BRSPDSN) Mahatmiya is to open an Artne Coffee Shop that is fully managed by blind people. Culinary products resulting from the training are sold at the shop at a price that is as you wish. In this study, the author is interested in further examining the role of BRSPDSN Mahatmiya in fostering an entrepreneurial spirit and its implications. The results of the study indicate that the Artne Coffee program plays an important role in empowering entrepreneurship among blind sensory disabled people. This program provides practical experience for beneficiaries in running a business, as well as increasing economic independence. The success of this program inspires other disabled people to explore their entrepreneurial potential. In addition, this program helps change public perceptions about blind sensory disabled people and creates an inclusive environment. The Artne Coffee program at BRSPDSN is a successful example of empowering entrepreneurship for people with disabilities. The implications of this program include inspiration for people with disabilities, changes in public perception, improving the quality of life, and becoming a model of empowerment that can be adopted by other institutions.